Evolution Over Time of Ventilatory Management and Outcome of Patients With Neurologic Disease*. Issue 7 (23rd February 2021) - Tejerina, Eva E.; Pelosi, Paolo; Robba, Chiara; Peñuelas, Oscar; Muriel, Alfonso; Barrios, Deisy; Frutos-Vivar, Fernando; Raymondos, Konstantinos; Du, Bin; Thille, Arnaud W.; Ríos, Fernando; González, Marco; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To describe the changes in ventilator management over time in patients with neurologic disease at ICU admission and to estimate factors associated with 28-day hospital mortality. DESIGN: Secondary analysis of three prospective, observational, multicenter studies. SETTING: Cohort studies conducted in 2004, 2010, and 2016. PATIENTS: Adult patients who received mechanical ventilation for more than 12 hours. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Among the 20, 929 patients enrolled, we included 4, 152 (20%) mechanically ventilated patients due to different neurologic diseases. Hemorrhagic stroke and brain trauma were the most common pathologies associated with the need for mechanical ventilation. Although volume-cycled ventilation remained the preferred ventilation mode, there was a significant ( p < 0.001) increment in the use of pressure support ventilation. The proportion of patients receiving a protective lung ventilation strategy was increased over time: 47% in 2004, 63% in 2010, and 65% in 2016 ( p < 0.001), as well as the duration of protective ventilation strategies: 406 days per 1, 000 mechanical ventilation days in 2004, 523 days per 1, 000 mechanical ventilation days in 2010, and 585 days per 1, 000 mechanical ventilation days in 2016 ( p < 0.001). There were no differences in the length of stay in the ICU, mortality in the ICU, and mortality in hospital from 2004 to 2016. Independent risk factors for 28-day mortality were age greater than 75 years, Simplified Acute Physiology Score II greater than 50, the occurrence of organ dysfunction within first 48 hours after brain injury, and specific neurologic diseases such as hemorrhagic stroke, ischemic stroke, and brain trauma. CONCLUSIONS: More lung-protective ventilatory strategies have been implemented over years in neurologic patients with no effect on pulmonary complications or on survival. We found several prognostic factors on mortality such as advanced age, the severity of the disease, organ dysfunctions, and the etiology of neurologic disease.